Etika Lingkungan Sastra Digital Madura serta Pemanfaatannya dalam Pembelajaran - Raudlatul Jannah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The relationship between nature and literary works has given birth to a concept regarding ecological issues in literature. Ecocriticism depicts the connection between humans and the environment in all cultural aspects, and it can even address ecological issues. The purpose of this research is to examine the environmental ethics values found in the short story collection 'Rokat Tase' by Muna Masyari and how they can be utilized in Indonesian language learning. This study is a qualitative descriptive research with quotation data from the short story texts containing environmental elements. The data analysis technique used is the ecocritical analysis approach with an ethical study model. The research steps consist of data collection, data reduction, presenting data, and drawing conclusions. The research results show that there are 5 environmental ethics values, namely respect for nature, cosmic solidarity, the principle of compassion and concern for nature, the principle of non-harm, and the principle of simple living in harmony with nature. As per the objectives of literature learning in the 10th-grade Merdeka curriculum, where students are expected to connect and appreciate the values contained in literary works, the values found in the short stories by Muna Masyari can be utilized as important teaching materials to address the environmental issues faced by humanity.